Review Literature: Human Capital improvement to increase customer satisfaction at the Ministry of Finance Republic of Indonesia - Muawanah, Roisatul (Prosiding Seminar, 2022)
the purpose of this study is to know how the program of education and training of employees in Ministry of Finance has been successful. Is there any obstacle that need to pay attention with the improvement? How to improve capacity and skills of human capital at the Ministry of Finance Republic of Indonesia in the best way. Ministry of Finance is the leading Ministry among other Ministries in Republic of Indonesia, that deliver services to the stakeholder. This makes a lot of efforts of improvements need to be done in each area every time. To deliver the best data to support fundamental decision to the government of Republic of Indonesia in economic sector. Improving human capital capacity is the most effective way to speed up the quality of services and data that are needed. The method of this study used qualitative review. An observation was conducted on the websites, literatures, data from Ministry of Finance and in the internet about human capital of Ministry of Finance.